Evaluation of Cowpea Morpho-physiological and Yield Responses to Vegetative and Pre-Anthesis Water-Deficit Stress Tolerance under Greenhouse Conditions - Ritte, Inocent; Egnin, Marceline; Idehen, Osagie; Mortley, Desmond; Bernard, Gregory; Binagwa, Papias; Brown, Adrianne; Bonsi, Conrad (European Journal of Applied Sciences, 2022)
Cowpea production is severely hindered by water scarcity; thus, understanding morpho-physiological response mechanisms of known drought-tolerant cultivars under water-deficit stress is critical to identify and establish representative yield-related traits of climate-hardy cowpeas. To determine cowpea genotypic variability to drought-tolerance, seventeen days-post sowing (DPS) greenhouse plants were subjected to 14-days drought stress without watering, then watered every 10-days at 25%, 50%, and 75% field capacity (FC) until maturity in two-trial experiments. Controls were well-watered at 100% FC every 3-days. Drought stress data were collected on plant height, stem diameter, chlorophyll content and terminal leaflet expansion rate. At maturity, 83 to 119 DPS, pod number, shoot and root biomass, and seed yield per plant were recorded. Data were combined and analyzed using analysis of variance. Drought tolerance was evaluated by percent change in performance and stress tolerance indexes. Drought stress in both trials impacted phenotypic expression. Plant height declined by 74%, stem diameter 18.2%, chlorophyll content, 47.6% terminal leaf length 83.2%, and width 85.2%. Pods per plant were reduced by 73% and seed yield by 98.8%. The estimated correlation between morpho-physiological and other yield-related traits of drought-tolerance indices verified that TVu 11987, LOBIA-I-SEFADE, and TVu 7362 were drought tolerant along with confirmed tolerant commercial cultivars California Blackeye No.5, Big Boy, and Lady. These cultivars exhibited different stress-coping strategies of low water requirements and growth performance to yield reduction. Overall, the genotypic performance recorded as drought-tolerant characteristics may be recommended as potential screening factors for donor cultivar traits in cowpea breeding programs.